DNA Splicing Language Predictor - Lim, Wen Li; Yuhani, Yusof; Norhayati, Rosli (2014)
Recombinant DNA technology, joining two DNA molecules together to produce new genetic combinations is of value to medicine, agriculture and science industry. This new invention of software programming has been developed using Visual Basic in order to predict the number pattern of resulted molecules after the cut and paste phenomenon of two double-stranded DNA, based on the theorems that have been formulated by using Y-G splicing system. Besides, the characteristics of restriction enzymes in terms of palindromic and inverse complement properties are also determined